Genetic variants of small airways and interstitial pulmonary disease in children - Mohammed T. Alsamri; Amnah Alabdouli; Alia M. Alkalbani; Durdana Iram; Mohamed I. Tawil; Priya Antony; Ranjit Vijayan; Abdul-Kader Souid (Scientific Reports, 2021)
Abstract Genetic variants of small airways and interstitial pulmonary disease have not been comprehensively studied. This cluster of respiratory disorders usually manifests from early infancy (‘lung disease in utero’). In this study, 24 variants linked to these entities are described. The variants involved two genes associated with surfactant metabolism dysfunction (ABCA3 and CSF2RB), two with pulmonary fibrosis (MUC5B and SFTP), one with bronchiectasis (SCNN1B), and one with alpha-1-antitrypsin deficiency (SERPINA1). A nonsense variant, MUC5B:c.16861G > T, p.Glu5621*, was found in homozygous state in two siblings with severe respiratory disease from birth. One of the siblings also had heterozygous SFTPA1:c.675C > G, p.Asn225Lys, which resulted in a more severe respiratory disease. The sibling with only the homozygous MUC5B variant had lung biopsy, which showed alveolar simplification, interstitial fibrosis, intra-alveolar lipid-laden macrophages, and foci of foreign body giant cell reaction in distal airspaces. Two missense variants, MUC5B:c.14936 T > C, p.Ile4979Thr (rs201287218) and MUC5B:c.16738G > A, p.Gly5580Arg (rs776709402), were also found in compound heterozygous state in two siblings with severe respiratory disease from birth. Overall, the results emphasize the need for genetic studies for patients with complex respiratory problems. Identifying pathogenic variants, such as those presented here, assists in effective family counseling aimed at genetic prevention. In addition, results of genetic studies improve the clinical care and provide opportunities for participating in clinical trials, such as those involving molecularly-targeted therapies.